Aberrant heterochromatin silences immune response genes in chronic lymphocytic leukemia - Olivia M. Depies; Qianqian Guo; Yuan Gao; Sutapa Sinha; Zhenqing Ye; Weiguo Han; Kari G. Rabe; Mingma S. Hoel; Heather C. Darby; Chuanhe Yu; Esteban Braggio; Sameer A. Parikh; et al. (Blood Neoplasia)
Abstract: Epigenetic alterations have been found in chronic lymphocytic leukemia (CLL), but the functional importance of these changes remains underexplored. Here, we characterized the genome-wide histone modification landscapes of CLL using patient-derived samples across the disease course. Compared with normal B cells, we found that the enhancers specifically lost in CLL B cells are associated with the downregulation of genes involved in immune response. Importantly, these lost enhancers exhibit an increased level of heterochromatin marks, including H3K9me3 and H3K27me3. Using the EBF1 gene locus as an example, we demonstrated that acquired H3K9me3 contributes to enhancer silencing and associated gene suppression. We further found that this aberrant chromatin signature also exists in the CLL precursor stage monoclonal B-cell lymphocytosis (MBL) cells, implicating the importance of epigenetic silencing in CLL evolution. Finally, when treated with the Bruton tyrosine kinase inhibitor ibrutinib, these silenced enhancers are relatively stable during therapy compared with the CLL-gained enhancers. In summary, we described an epigenetic silencing mechanism mediated by the heterochromatin that persists throughout CLL disease development and treatment and which may increase the risk of severe infections in MBL and CLL.